Patterns Thematic Tracing of the Hadith of the Prophet Muhammad SAW Using the FP-Growth Algorithm and ECLAT - Nurbojatmiko, Nurbojatmiko; Rustamaji, Eri; Wadud, Abdul; Mutholib, Abdul (Applied Information System and Management (AISM), 2024)
The limited ability to memorize, understand Arabic, and access sources are obstacles to understanding Islamic knowledge, especially hadith. Searching for access to sources to obtain hadiths that are in accordance with the theme and the interrelationships between themes improves the quality of the preachers towards religious understanding. This study investigates how to automate the thematic tracking pattern of Prophet Muhammad's hadith using the FP-Growth (Frequent Pattern-Growth) and ECLAT algorithms. The research was conducted using qualitative and quantitative approaches. The next step involves creating a prototype using the dataset development framework. The result of this study is a prototype of hadith tracing using the FP-Growth algorithm with the prophet's hadith dataset based on the Bulughul Maram book.